Determination of Heirs in Islamic Civil Law in Indonesia: A Case Study of Decision Number 8/Pdt.P/2024/PA.Plk of the Palangka Raya Religious Court - Dewi Puruhita Suci; Mutiara Dewi Lestari (Annujum: Journal of Humaniora and Law, 2026)
Inheritance law is a crucial aspect of Islamic family law as it concerns the continuation of property rights after a person’s death. In Indonesia, Islamic inheritance law has been formally codified through the Compilation of Islamic Law (KHI), yet in practice, the determination of heirs is often required not only to resolve family disputes but also for administrative purposes such as bank account settlement or insurance claims. This article aims to analyze the application of Islamic inheritance law through the case study of Decision Number 8/Pdt.P/2024/PA.Plk at the Palangka Raya Religious Court regarding a petition for the determination of heirs of a deceased who left behind a wife and children. This study employs a normative juridical approach and library research, with descriptive-analytical methods. The findings indicate that the panel of judges confirmed the wife and three children as legal heirs based on the provisions of the Qur’an, hadith, and Articles 171–177 of the KHI, while ensuring no impediments to inheritance as regulated in Article 173 of the KHI. The ruling aligns with the principles of faraidh and demonstrates that Islamic inheritance law can operate in harmony with Indonesia’s legal system, particularly in providing legal certainty for heirs in administrative matters.